Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan pada CV. Gudang Cell Tasikmalaya - Nurul Nurrohmah Ainul Yakin; Rita Tri Yusnita; Arga Sutrisna (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research was conducted with the aim of knowing the effect of motivation and work discipline on employee performance at CV. Tasikmalaya Cell Warehouse. The method used in this research is the causality method with a quantitative approach. Data collection techniques were obtained directly through questionnaires distributed to 94 respondents who were employees of CV. Tasikmalaya Cell Warehouse. The data analysis tool used in this research is path analysis. Based on the results of the study, it can be seen that: (1) Motivation has a positive and significant effect on Work Discipline on CV. Cell Warehouse in Tasikmalaya; (2) Motivation directly has a positive but not significant effect on Employee Performance on CV. Cell Warehouse in Tasikmalaya; (3) Work Discipline directly has a positive and significant effect on Employee Performance on CV. Cell Warehouse in Tasikmalaya; (4) Motivation has a positive and significant effect on Employee Performance through Work Discipline on CV. Tasikmalaya Cell Warehouse.